The role of transformational leadership in enhancing employee performance in the digital era: human resource management - Sewang, Sewang (International Journal of Enterprise Modelling, 2025)
This study explores the role of transformational leadership in improving employee performance during digital transformation at PT Kawasan Industri Makassar (PT KIMA), an industrial estate management company in Indonesia. Using a qualitative case study approach, data were collected through interviews with eight managers and key employees, participatory observation, and document analysis. Findings reveal that the four dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—enhance employee adaptability to digital systems, foster interdepartmental collaboration, and improve operational efficiency. Practically, the study suggests the importance of leadership development programs incorporating digital skills and emotional intelligence to support organizational change. Theoretically, it contributes to digital leadership literature by framing transformational leadership within industrial management in a developing country context. The results highlight the necessity of adaptive leadership to manage technological disruption and optimize human resource performance in the digital era.